2021
DOI: 10.3390/molecules26092464
|View full text |Cite
|
Sign up to set email alerts
|

Isomaltulose Exhibits Prebiotic Activity, and Modulates Gut Microbiota, the Production of Short Chain Fatty Acids, and Secondary Bile Acids in Rats

Abstract: In vitro experiments have indicated prebiotic activity of isomaltulose, which stimulates the growth of probiotics and the production of short chain fatty acids (SCFAs). However, the absence of in vivo trials undermines these results. This study aims to investigate the effect of isomaltulose on composition and functionality of gut microbiota in rats. Twelve Sprague–Dawley rats were divided into two groups: the IsoMTL group was given free access to water containing 10% isomaltulose (w/w), and the control group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 61 publications
(76 reference statements)
0
19
0
Order By: Relevance
“…In line with our results, it has been reported that the administration of FOS and FOS-enriched inulin to rats has a direct effect on bone, increasing both micro (cortical and trabecular parameters) and macrostructure (BMD and BMC) in processes of growth, development, and osteoporosis [ 54 ]. Similarly, a recent study reported that the administration of isomaltulose elevates the relative abundance of Actinobacteria, and notably increases the production of SCFA, particularly propionic acid and, to a lesser extent, butyric acid [ 55 ]. Propionate and butyrate have been shown to modulate bone homeostasis by increasing bone mass and decreasing bone resorption [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, it has been reported that the administration of FOS and FOS-enriched inulin to rats has a direct effect on bone, increasing both micro (cortical and trabecular parameters) and macrostructure (BMD and BMC) in processes of growth, development, and osteoporosis [ 54 ]. Similarly, a recent study reported that the administration of isomaltulose elevates the relative abundance of Actinobacteria, and notably increases the production of SCFA, particularly propionic acid and, to a lesser extent, butyric acid [ 55 ]. Propionate and butyrate have been shown to modulate bone homeostasis by increasing bone mass and decreasing bone resorption [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hao et al ( 61 ) found that Shuttleworthia was highly positively correlated with MCP and short-chain VFA production in postweaning calves. However, Shuttleworthia is a pathogen in the gut of rats, and its level decreases when rats are fed prebiotic isomaltulose ( 62 ). Ruminal microbiota are complex and interactive, and the role of Shuttleworthia in ruminants and monogastric animals needs to be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of gut microbiota can be changed by antibiotics ( 112 ), prebiotics ( 113 ), probiotics ( 114 ), or microflora transplantation ( 115 ). The treatment of EC by regulating the microflora may become a novel treatment method.…”
Section: Harnessing Microbiota For Esophageal Cancer Therapy-related Applicationsmentioning
confidence: 99%